Conjugate‐Driven Electron Density Delocalization of Piperidine Nitroxyl Radical for Stable Aqueous Zinc Hybrid Flow Batteries. Issue 17 (28th February 2022) - Fan, Hao; Hu, Bo; Li, Hongbin; Ravivarma, Mahalingam; Feng, Yangyang; Song, Jiangxuan
Abstract: Stable and soluble redox‐active nitroxyl radicals are highly desired for high‐capacity and long‐life aqueous zinc hybrid flow batteries (AZHFBs). Here we report a "π–π" conjugated imidazolium and "p–π" conjugated acetylamino co‐functionalized 2, 2, 6, 6‐tetramethylpiperidine‐N‐oxyl (MIAcNH‐TEMPO) as stable catholyte for AZHFBs. The incorporation of double‐conjugate substituents could delocalize the electron density of the N−O head and thus remarkably stabilize the radical and oxoammonium forms of TEMPO, avoiding the side reaction of ring‐opening. Consequently, the applied MIAcNH‐TEMPO/Zn AZHFB demonstrates the hardly time‐dependent stability with a constant capacity retention of 99.95 % per day over 16.7 days at a high concentration catholyte of 1.5 M and high current density of 50 mA cm −2 . This proposed molecular engineering strategy based on electron density regulation of redox‐active structures displays an attractive efficacy and thus represents a remarkable advance in high‐performance AZHFBs. Abstract : An acetylamino and imidazole co‐functionalized 2, 2, 6, 6‐tetramethylpiperidine‐N‐oxyl (MIAcNH‐TEMPO) catholyte for aqueous zinc hybrid flow batteries (AZHFBs) is reported. The "p–π" and "π–π" double‐conjugate structure design delocalizes the electron density of the N−O head and thus inhibits electrophilic/nucleophilic attacks corresponding to N−O⋅/ + N=O forms. The applied 1.5 M MIAcNH‐TEMPO‐based AZHFB exhibits a high capacity retention rate of 99.95 % per day at 50 mA cm −2 .